Contato com gatos: um fator de risco para a toxoplasmose congênita? - Montaño, Patrícia Yukiko; Cruz, Marúcia de Andrade; Ullmann, Leila Sabrina [UNESP]; Langoni, Helio [UNESP]; Biondo, Alexander Welker (My University, 2010)
Toxoplasmosis is an important zoonosis and one of the most common parasitic infections throughout the world, which may cause among other problems several fetal pathologic alterations. Congenital toxoplasmosis is a result of transplacental transmission of Toxoplasma gondii due to a prime infection of the mother during pregnancy. Several studies have determined that the main risk factor for infection in pregnant women is the consumption of uncooked meat, which contributed from 30 to 63% of cases; other 6% to 17% of infections were related to contaminated soil. The relationship between pregnant women and their cats constitutes nothing more than a healthy experience when main transmission mechanisms and risk factors related to the disease are known.

La toxoplasmosis es una importante zoonosis y una de las infecciones parasitarias más comunes en todo el mundo, que puede causar entre otros problemas diversas alteraciones patológicas en el feto. La toxoplasmosis congénita resulta de la transmisión transplacentaria de Toxoplasma gondii debido a la primoinfección de la madre durante la gestación. Varios estudios determinaron que el principal factor de riesgo para la infección en gestantes es el consumo de carne mal cocida, que contribuyó con el 30 a 63% de los casos; otros 6% a 17% de las infecciones se relacionaron con suelo contaminado. La convivencia entre gestantes y sus gatos constituye nada más que una sana experiencia cuando se conocen los principales mecanismos de transmisión y los factores de riesgo relacionados con la enfermedad.

A toxoplasmose é uma importante zoonose e uma das infecções parasitárias mais comuns em todo o mundo, que pode causar, entre outros problemas, diversas alterações patológicas fetais. A toxoplasmose congênita é resultante da transmissão transplacentária do Toxoplasma gondii, devido à primoinfecção da mãe durante a gestação. Vários estudos determinaram que o principal fator de risco para a infecção de gestantes é o consumo de carne mal cozida, que contribuiu com 30% a 63% dos casos outros 6% a 17% das infecções foram relacionados ao solo contaminado. O convívio entre gestantes e seus gatos constitui nada mais do que uma experiência saudável quando se tem conhecimento dos principais mecanismos de transmissão e dos fatores de risco correlacionados com a doença.
Contact with cats: a risk factor for congenital toxoplasmosis?
Contacto con gatos: ¿un factor de riesgo para la toxoplasmosis congénita?
Keywords: Pregnancy; Toxoplasma gondii; Gestación; Zoonose; Gestação; Toxoplasma gondii